Screening and evaluation of entomopathogenic fungi against the bean bug, Riptortus pedestris using multiple tools. Issue 11 (10th November 2022) - Win, Thida; Lee, Jin Yong; Woo, Ra Mi; Woo, Soo Dong
Abstract: The bean bug Riptortus pedestris causes major damage to soybean and has become a serious problem due to its high resistance to insecticides. To address this problem, this study aimed to select the most effective entomopathogenic fungi for the control of R. pedestris . Selection was performed through the evaluation of virulence, thermotolerance, and UV‐B tolerance of fungal isolates against R. pedestris and conidial production on grain medium. The pathogenicity of 30 Beauveria bassiana isolates and 30  Metarhizium anisopliae isolates was evaluated, and pathogenicity was confirmed in all but 3 isolates of B. bassiana . Among the 57 isolates, 11 exhibited high virulence. Of these 11 isolates, B. bassiana JB13G1W1 and M. anisopliae CB6T1G1 and JB12R3G1 showed the highest virulence of more than 80%. The conidial production of all fungal isolates in millet grain medium was good, ranging from 10 8 to 10 9 conidia/g. The UV‐B tolerance and thermotolerance of the 57 isolates varied according to the isolate, and those of M. anisopliae isolates were slightly higher than those of B. bassiana . As a result of comparative evaluation of the virulence, conidial production, thermotolerance, and UV‐B tolerance of fungal isolates, B. bassiana JB13G1W1 and M. anisopliae CB6T1G1 and JB12R3G1 were selected as excellent fungal isolates for the control of R. pedestris . Among them, B. bassiana JB13G1W1 showed the highest virulence, with LC50 and LT50 values of 7.86 × 10 5 conidia/mL and 5.24 days at 10 8 conidia/mL, respectively. The most effective growth stage to control R. pedestris with B. bassiana JB13G1W1 was 2nd‐instar nymphs.